Efektivitas Model Pembelajaran Problem Based Learning dan Project Based Learning terhadap Kemampuan Berpikir Kritis Matematika SMP - Ikvina Alrin Aulia Bilqiis; M. Saifuddin Zuhri; Muhtarom Muhtarom (Jurnal Kualita Pendidikan, 2023)
Mathematics is a subject that gets special attention because it is the most important field of study and the basis for studying other sciences. The Problem Based Learning learning model is learning that is used to stimulate students' critical thinking skills and the Project Based Learning model is learning activities that use projects as a learning process to achieve attitude, knowledge and skill competencies. The research method uses experiments with a True Experimental Design in the form of a Posttest-Only Control Design. The sample in this study used a cluster random sampling technique, with a sample of three classes from all class VIII SMPN 20 Semarang. The data collection techniques used are tests, documentation and observation. The results showed that there were differences in students' critical thinking abilities with the Problem Based Learning model, Project Based Learning model and conventional learning, where students' critical thinking skills with the Problem Based Learning model (p=0.000) and the Project Based Learning model (p=0.016) were more better than the conventional learning model, but students with the Problem Based Learning learning model and the Project Based Learning model showed no difference in critical thinking skills (p=0.117).